2014
DOI: 10.1186/scrt411
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived stem cell transplantation as a potential therapy for collagen VI-related congenital muscular dystrophy

Abstract: IntroductionCongenital muscular dystrophies (CMD) are a clinically and genetically heterogeneous group of neuromuscular disorders characterized by muscle weakness within the first two years of life. Collagen VI-related muscle disorders have recently emerged as one of the most common types of CMD. COL6 CMD is caused by deficiency and/or dysfunction of extracellular matrix (ECM) protein collagen VI. Currently, there is no specific treatment for this disabling and life-threatening disease. The primary cellular ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 41 publications
(52 reference statements)
0
55
0
Order By: Relevance
“…The presence of ADSCs in lipomas with a differentiation potential similar to that of regular ADSCs has been shown in previous studies [11,12,16,17]. Potentially, ADSCs from useless tissue may be an attractive cell source for the application of regenerative medicine [18]. The cells residing in fat stroma revealed a wide range of functional properties in vivo as well as differentiation potential in vitro.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The presence of ADSCs in lipomas with a differentiation potential similar to that of regular ADSCs has been shown in previous studies [11,12,16,17]. Potentially, ADSCs from useless tissue may be an attractive cell source for the application of regenerative medicine [18]. The cells residing in fat stroma revealed a wide range of functional properties in vivo as well as differentiation potential in vitro.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, stem cell-based therapy hold promise for treating acquired and genetic diseases and has been utilized in animal models and human clinical trials, such as wound healing, tissue repair, cardiovascular disorders [19], congenital muscular dystrophy [18] or lower genito-urinary dysfunction [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multipotent mesenchymal stem cell (MSC) is the most common type of adult stem cells and is isolated from several sources such as bone marrow and adipose tissue. Another report has recently shown that transplanted human adipose-derived stem cells, with phenotypic and functional features of mesenchymal progenitors, secrete collagen VI protein in Col6a1 −/− mice 59. Thus, MSC-based therapy can be an attractive option as transplanted cells are able to self-renew and to differentiate into collagen VI-producing cells in skeletal muscle 41 42…”
Section: Molecular Diagnosis Pathogenesis and Therapeutic Avenuesmentioning
confidence: 99%
“…22 Moreover, they have been applied to repair muscle tissues and restore tissue vascularization. 25 As for ED therapy, independent groups have investigated the feasibilities and advantages of ADSCs in rat models of DMED, cavernous nerve injury, and Peyronie's disease. 16,26,27 These results were encouraging but the traditional single-cell-based injection was relative preliminary, and the therapeutic potential was hampered by poor retention rate due to the blood flow.…”
Section: Discussionmentioning
confidence: 99%